Impact of Trade Openness in Industrial Productivity and Growth Competition in South Asia (Economic Journal of Nepal, 2014)
This paper investigates the impact of trade openness on the industrial productivity and growth in South Asia. Besides, education and training, human resource and investment, trade openness give rise the industrial productivity in South Asian Countries. In this study, it is found that the south Asian countries are not matured to create industrial productivity, trade creation and physical efficiency as they have plenty of potentiality of resources. Based on cross fixed effect model which is suitable for an panel data analysis, time series and cross sectional, this study covers time frame for the period of 1980-2013. Following pooled least squares and fixed effects estimation techniques, models are estimated using the fixed effects estimation. Fixed effect is tested through the sum of sequence of F-Test and chi- square test besides study has observed correlation among the concerned variables. In this empirical analysis, south Asian countries are taken in order to oversee into industrial productivity and growth competition.